Amnesia : clinical, psychological and medicolegal aspects - Whitty, Charles William Michael (Butterworths, 1977)
Amnesia: Clinical, Psychological and Medicolegal Aspects, 2nd Edition explores the clinical, psychological, and medicolegal aspects of amnesia. Experimental studies of the organic amnesic syndrome are presented and memory disorders associated with electroconvulsive therapy (ECT) are described. The role of amnesia in cerebral disease, the neuropathology of amnesic states, and psychogenic memory loss are also considered. This book is comprised of 11 chapters and begins with a discussion on experimental studies of the organic amnesic syndrome, along with certain associated studies of normal memor.